การกำกับดูแลร่วมทางการพยาบาลตามการรับรู้ของพยาบาลในงานการพยาบาลผู้ป่วยพิเศษ โรงพยาบาลมหาราชนครเชียงใหม่ - เจษฎา เทพศิริ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Nursing shared governance is a management structure that allows nurses to participate in decision-making in the organization. The objective of this study was to explore the perception of nursing shared governance and study the promoting factors and obstacle factors of nursing shared governance among nurses in the Private Nursing Department, Maharaj Nakorn Chiang Mai Hospital. The population in this study was 132 professional nurses. Research instruments were a questionnaire that includes the Index of Professional Nursing Governance developed by Hess (2010), translated into Thai by Natanong Pitchayakun (2019), and open questions about promoting factors and obstacle factors of nursing shared governance. The data was analyzed by descriptive statistics, including frequency, percentage, mean, and standard deviation. The results of the study are as follows: 1. The score of nursing shared governance illustrated the perception of inequality in shared decisions by staff nurses and nursing administrators in the control over personnel (μ = 38.00, σ = 14.11) and participation in committee structure (μ = 24.05, σ 7.92), whereas decisions were demonstrated to be perceived as equally shared by staff nurses and nursing administrators in access to information (μ = 36.80, σ = 10.29), influence over resources that support the practice (μ = 31.08, σ = 47.16), control over professional practice (μ = 35.78, σ = 10.06), and goal setting & conflict resolution (μ = 17.61, σ = 5.89). 2. Nurses reported that promoting factors of nursing shared governance included the use of 360-degree feedback, having access to various hospital communication channels, giving time and opportunity to join hospital meetings, and promoting knowledge among nurses. The obstacle factors of nursing shared governance included inconvenience in accessing information, high workload, and insufficient nursing staff. The results of this study will benefit nursing administrators in promoting nursing shared governance in the Private Nursing Department, Maharaj Nakorn Chiang Mai Hospital.